Extending the application potential of capillary electrophoresis/frontal analysis for drug-plasma protein studies by combining it with mass spectrometry detection - Mlčochová, Hana; Michalcová, Lenka; Glatz, Zdeněk (Electrophoresis, 2022)
CE/frontal analysis (CE/FA) is probably one of the most frequently used modes of CE for studying affinity interactions. It is typically performed with classic UV-Vis detection that suffers from low concentration sensitivity. To overcome this limitation, the applicability of CE/FA in combination with ESI-MS detection for the investigation of drug-HSA interactions was demonstrated. The developed new method combines the advantages of CE/FA, such as low sample consumption and no labeling or immobilization of interacting partners, with the benefits of MS detection, such as higher selectivity and sensitivity; moreover, it can be used for molecules lacking a fluorophore or chromophore. The binding parameters of tolbutamide (TL) and glimepiride (GLP), first- and second-generation antidiabetics that differ strongly in their solubility in aqueous solutions, were investigated by this CE/FA-MS method. This method, in contrast to the CE/FA method with the most commonly used UV-Vis detection, is more sensitive; an almost three times lower LOD was reached. The binding parameters of TL and GLP were investigated by this CE/FA-MS method and compared with the literature data. The binding constant value of TL obtained by UV-Vis detection was lower than the value obtained by the method hyphenated with MS detection, which is probably given by the influence of the ESI parameters on the stability of drug-HSA complex. In addition, the ratio of TL and HSA concentrations was divergent in both of the experimental approaches. Finally, it can be concluded that both detection methods have their strengths and weaknesses.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Blood Proteins; voda; hmotnostní spektrometrie s elektrosprejovou ionizací; krevní proteiny; Water; Electrophoresis, Capillary; Spectrometry, Mass, Electrospray Ionization; elektroforéza kapilární